2017
DOI: 10.1142/s0218863517500345
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity attosecond pulse generation by using inhomogeneous laser field in frequency and space

Abstract: High-order harmonic spectra and attosecond source generation from Ar atom driven by the inhomogeneous laser¯eld in frequency and space have been theoretically investigated. The results showed that (i) for the case of the frequency modulation of the laser, the harmonic cuto® can be remarkably extended with the introduction of the chirp of the laser¯eld, (ii) for the case of the space modulation of the laser, the harmonic cuto® can be further extended by using the positive spatial inhomogeneous¯eld, (iii) by pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Moreover, the high-intensity harmonic yield is favorable for the enhancement of the signal intensity of the SAPs. Generally, the harmonic yield can be enhanced with the assistance of the UV pulse [44,45], noise field [46] and THz field [47,48], etc. Recently, the investigations of the HHG from H + 2 or H 2 have shown that the harmonic yield is relevant to the nuclear correlation function [49] and can be enhanced as the initial vibrational state increases [50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the high-intensity harmonic yield is favorable for the enhancement of the signal intensity of the SAPs. Generally, the harmonic yield can be enhanced with the assistance of the UV pulse [44,45], noise field [46] and THz field [47,48], etc. Recently, the investigations of the HHG from H + 2 or H 2 have shown that the harmonic yield is relevant to the nuclear correlation function [49] and can be enhanced as the initial vibrational state increases [50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…5 Terahertz waves was also proposed for enhancement of harmonic yield of high harmonic generator for producing attosecond XUV and X-ray pulse. 6 For developing terahertz system, sources and detectors are not the only components. Terahertz absorbers, 7 modulators, 8 splitters, 8 waveguides, 5,9 planar circuits, 8 etc.…”
Section: Introductionmentioning
confidence: 99%